4D computed tomography scans for conformal thoracic treatment planning: is a single scan sufficient to capture thoracic tumor motion?. (17th January 2018) - Tseng, Yolanda D; Wootton, Landon; Nyflot, Matthew; Apisarnthanarax, Smith; Rengan, Ramesh; Bloch, Charles; Sandison, George; St. James, Sara
Abstract: Four dimensional computed tomography (4DCT) scans are routinely used in radiation therapy to determine the internal treatment volume for targets that are moving (e.g. lung tumors). The use of these studies has allowed clinicians to create target volumes based upon the motion of the tumor during the imaging study. The purpose of this work is to determine if a target volume based on a single 4DCT scan at simulation is sufficient to capture thoracic motion. Phantom studies were performed to determine expected differences between volumes contoured on 4DCT scans and those on the evaluation CT scans (slow scans). Evaluation CT scans acquired during treatment of 11 patients were compared to the 4DCT scans used for treatment planning. The images were assessed to determine if the target remained within the target volume determined during the first 4DCT scan. A total of 55 slow scans were compared to the 11 planning 4DCT scans. Small differences were observed in phantom between the 4DCT volumes and the slow scan volumes, with a maximum of 2.9%, that can be attributed to minor differences in contouring and the ability of the 4DCT scan to adequately capture motion at the apex and base of the motion trajectory. Larger differences were observed in the patients studied, up to a maximum volume difference of 33.4%. These results demonstrate that a single 4DCT scan is not adequate to capture all thoracic motion throughout treatment.